Microstructural and Electrical Properties of Sn-Modified BaTiO3 Lead-Free Ceramics by Two-Step Sintering Method - Wichita Kayaphan; Pornsuda Bomlai (Advances in Materials Science and Engineering)
Ba(Ti0.92Sn0.08)O3 lead-free ceramics were prepared using a two-step sintering (TSS) technique. Varying the first sintering temperature T1 (1400 and 1500°C) and the dwell time t1 (0, 15, and 30 min), we obtained dense ceramics which were then soaked at a constant temperature of 1000°C (T2) for 6 h (t2). The structural and electrical properties were investigated. XRD results indicated that all the ceramics showed a pure perovskite phase with tetragonal symmetry. Density and grain size increased with higher T1 temperatures and increased t1 dwell times. Enhanced electrical properties were achieved by sintering at the optimized T1 sintering temperature and t1 dwelling time. At the lower T1 sintering temperature of 1400°C, the dielectric and piezoelectric properties and the Curie temperature of the ceramics were improved significantly by increasing t1 dwell time. Further, increasing the sintering temperature T1 to 1500°C, excellent properties were obtained at t1 = 15 min which then deteriorated when t1 was increased to 30 min. The electrical properties of the sample sintered under the T1/t1/T2/t2 condition of “1500/15/1000/6” showed the best values. For this sample the piezoelectric coefficient (d33), dielectric permittivity (εr), loss factor (tanδ), and Curie temperature (TC) were 490 pC/N, 4385, 0.0272, and 48°C, respectively.